PENGARUH LOKASI, KUALITAS PELAYANAN DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA WARUNG BABI GULING PANDE EGI DI GIANYAR - Septyani, Putu; Triadhi, Nyoman Andika (Jurnal MBE Manajemen Bisnis, Equilibrium, 2023)
The aim of this study is to examine the partial and simultaneous influence of location, service quality and price perception on purchasing decisions at Warung Babi Guling Pande Egi in Gianyar. The sample was determined using a non-probability sampling method with a technique for determining the sample using accidental sampling with a total of 90 respondents. Validity Testing, Reliability, Classical Assumptions, Multiple Linear Regression, Coefficient of Determination, T Test and F Test were chosen as techniques for analyzing data. The results of this study are that location, service quality and price perception have a positive and significant influence, both partially and simultaneously, on purchasing decisions at the Pande Egi suckling pig stall in Gianyar.